In Search of the Holy Grail of Anticoagulant Therapy - Kuznar, Wayne (MD Conference Express, 2013)
The trade-off between antithrombotic effect and bleeding hinders the efficacy of current anticoagulant therapy. An antibody in development has demonstrated dissociation of the antithrombotic effect from the bleeding effect in preclinical studies, showing promise as a revolutionary drug for the treatment of thrombosis.